2020
DOI: 10.3389/fpsyg.2020.00245
|View full text |Cite
|
Sign up to set email alerts
|

Scales Used to Measure Job Stressors in Intensive Care Units: Are They Relevant and Reliable? A Systematic Review

Abstract: Background: Many studies have been conducted in intensive care units (ICUs) to identify the stress factors involved in the health of professionals and the quality and safety of care. The objectives are to identify the psychometric scales used in these studies to measure stressors and to assess their relevance and validity/reliability. Methods: All peer-reviewed full-text articles published in English between 1997 and 2016 and focusing on an empirical quantitative study of job stressors were identified through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
1
11
0
2
Order By: Relevance
“…Moreover, ICUs are characterised by self‐defining traumatic tasks in which professionals engage during their work hours (Filho et al, 2019), and at the same time, these professionals may deal with time constraints and social pressure while performing those tasks (Mason et al, 2014), linked with a high workload related to the critical caring task (van Mol et al, 2015). These work stressors are considered to be relevant in the consequences of working in ICU (Laurent et al, 2020). In contrast, there are few studies that delve more deeply into the difficulties that health professionals may encounter on the day‐level, despite its undeniable relevance (Yoder, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ICUs are characterised by self‐defining traumatic tasks in which professionals engage during their work hours (Filho et al, 2019), and at the same time, these professionals may deal with time constraints and social pressure while performing those tasks (Mason et al, 2014), linked with a high workload related to the critical caring task (van Mol et al, 2015). These work stressors are considered to be relevant in the consequences of working in ICU (Laurent et al, 2020). In contrast, there are few studies that delve more deeply into the difficulties that health professionals may encounter on the day‐level, despite its undeniable relevance (Yoder, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that complexity of care, ethics and the relationship with the patient and family are dimensions of stress that shape the identity of the unit and refer to strong emotional dimensions [ 7 , 35 , 36 ]. Therefore, it is essential to be able to take them into account when evaluating stress in the same way as more generic stressors, which is not possible with current generic scales such as the JCQ [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…They decided to merge some factors and rename others to obtain a single consensual typology of stressors. This expert panel then grouped all the stressors into broad categories guided by the literature [ 14 ], and complemented, in case of ambiguities, by the experience of clinicians.…”
Section: Phase 1: Identification Of Stressorsmentioning
confidence: 99%
See 2 more Smart Citations